ERROR ANALYSIS OF PROBLEM SOLVING IN CIRCLE SUBJECT FOR CLASS VIII-6 STUDENTS OF SMP NEGERI 3 MATARAM IN ACADEMIC YEAR 2019/2020 - Nur Asniati; Sri Subarinah; Amrullah (FKIP Universitas Mataram, 2022)
This study aims to determine: 1) the types of errors of students of class VIII-6 of SMP in solving problems with the circle subject. 2) the factors that cause students of class VIII-6 of SMP to make mistakes in solving problems with the circle subject. This research is classified as descriptive quantitative research. The population in this study were all students of class VIII-6 SMP which consisted of seven classes. The sampling technique used was simple random sampling. The research subjects were students of class VIII-6 SMP as many as 28 students. The research procedure used in this research is written test and interview. The test was used to analyze reading errors, comprehension errors, transformation errors, processing skills error and encoding error. Meanwhile, interviews are used to trace students mistakes in depth. The instrument testing conducted was a content validity tester in consultation with experts, namely mathematics teachers and leacturers. The result showed that there were 5 types of error categories committed by students of SMP, namely: 1) reading errors of 13,94% were in the low error category. 2) comprehension error of 47,61% is in the sufficient error category. 3) transformation error of 57,53% is in the sufficient error category. 4) process skills error as much as 66,66% in the high error category. 5) encoding error of 94,39% in the very high error category..